Sea cucumber extract TBL‐12 inhibits the proliferation, migration, and invasion of human prostate cancer cells through the p38 mitogen‐activated protein kinase and intrinsic caspase apoptosis pathway. Issue 8 (19th March 2019) - Yuan, Lei; Huang, Xubin; Zhou, Kai; Zhu, Xun; Huang, Bin; Qiu, Shaopeng; Cao, Kaiyuan; Xu, Lin
Abstract: Background: Sea cucumber is a kind of nutritious echinoderm that has multiple biological activities, including antioxidant, antibacterial, and antitumor activities. However, there is no extensive study on the antitumor effect of sea cucumber extract on prostate cancer (PCa). TBL‐12 is a new sea cucumber extract. In this study, we investigated the in vivo anti‐PCa effect of TBL‐12 and its in vitro effects on the proliferation, apoptosis, migration, and invasion of the human PCa cell lines LNCaP, 22RV1, PC‐3, and DU145, and evaluated its possible mechanisms. Methods: Cell proliferation was analyzed by cell counting kit‐8 and colony formation assays. Scratch migration assay and transwell invasiveness assay were used to observe TBL‐12 effect on the migration and invasion of PCa cells. Matrix metalloproteinase 2 (MMP‐2) and MMP‐9 expression and enzymatic activity was determined by Western blot analysis, quantitative reverse‐transcription polymerase chain reaction, and gelatin zymography. Apoptosis level was detected by flow cytometry analysis. Western blot analysis was used to analyze p38 mitogen‐activated protein kinase (MAPK) and apoptosis pathways. Angiogenic array analysis was used to explore autocrine and paracrine growth factors in PCa cell lines. Xenograft tumor model was built to observe the in vivo anticancer effect. Results: TBL‐12 could significantly inhibit tumor growth in xenograft PCa mice in vivo, and dramatically inhibit the proliferation, colony formation, migration, and invasiveness of PCa cells in vitro ( P < 0.05 and P < 0.001). The expression and enzyme activity of MMP‐2 and MMP‐9 were significantly suppressed by TBL‐12 ( P < 0.01), and decreased phosphorylation level of p38 in PCa cells was detected ( P < 0.001). Furthermore, TBL‐12 could reinforce the MMP‐2/MMP‐9 inhibitory effect of SB203580, a specific inhibitor of the p38 MAPK pathway ( P < 0.05). Besides, TBL‐12 could induce the apoptosis of PCa cells by activating caspase‐9, caspase‐7, and poly(ADP‐ribose) polymerase and suppressing survivin, and inhibit the secretion of angiogenin, angiopoietin‐2, and vascular endothelial growth factor in PCa cells. Conclusions: Sea cucumber extract TBL‐12 could suppress the proliferation and metastasis of human PCa cells by inhibiting MMP‐2 and MMP‐9 via blocking the p38 MAPK pathway, inducing apoptosis through intrinsic caspase apoptosis pathway and inhibiting the secretion of angiogenic factors. Our findings may be of importance and significance for the research and clinical applications of sea cucumber extract in PCa treatment.